The application of organic liquid fertilizer C. glomerata and NPK Phonska to enhance agronomic efficiency in maize cultivation on Alluvial soil - Jamilah, Jamilah; Aguswanto, Aguswanto; Ediwirman, Ediwirman; Sunadi, Sunadi; Novia, Prima (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2024)
Fertilization is crucial in maize cultivation, and inorganic fertilizers can be expensive. Therefore, it is essential to provide alternative fertilizers to reduce dependence on inorganic fertilizers. This study investigated the role of organic liquid fertilizer C. glomerata (OLFC) in increasing the efficiency of NPK Phonska fertilizer, influencing soil chemical reactions, and enhancing the growth and yield of maize on alluvial soils. The materials used were hybrid maize of the Pioneer 32, OLFC, and NPK Phonska (15-15-15). The experiment was arranged in a completely randomized design (CRD) in factorial. The OLFC was applied at 0 mL L-1, 5 mL L-1, and 10 mL L-1; NPK Phonska Fertilizer at 0, 150, and 300 kg ha-1 in three replications. The data obtained were statistically analyzed using ANOVA at 5%. Level of significance and mean separation using the LSD at 5% probability. The following parameters were evaluated: soil chemical properties and agronomic factors, such as the height of crop, net assimilation rate, relative growth rate, weight of 100 seeds, yield, and agronomic efficiency (AE). The highest maize yield recorded was 4.83 tons per hectare, achieved by applying 150 NPK Phonska kg per hectare, supported by a fertilization efficiency of 11.28%. Adding 5 mL per liter of OLFC every two weeks to maize plants resulted in the highest AE, reaching 21.81%.